The Theory and Practice of Equalization - Robin Boadway (Queen's University, Department of Economics, 2003)
This paper presents a selective and non-technical survey of the role of intergovernmental equalization transfers as a device for achieving efficiency in the allocation of labor across regions in a decentralized nation, and for achieving fiscal equity among residents of various regions. We discuss some of the issues that arise in attempting to put the principles of equalization into practice.
Keywords: H77; 330; Equalization; Intergovernmental Transfers